PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI UNTUK PENGENTASAN KEMISKINAN - Doni Aprianto Syaputra; Dibyana Galih Prakasita; Cindy Aulia; Desiree Roring; Faskan Aditama (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe purpose of this literature study is to determine the local, national and global impacts resulting from the Rumah Swadaya program in reducing poverty. The formulation of the problem in this paper is: What is the local, national and global impact resulting from the Self-Help Home Program in reducing poverty? ”. This research is a literature study of documents related to the Social Rehabilitation Program for Unfit for Living Houses for Poverty Alleviation. The conclusion of the study is that the Rumah Swadaya program has a positive impact on poverty alleviation and the welfare of poor families through improving the quality / standard of living of these families. The Rumah Swadaya program also indirectly eliminates marginalized groups, which gives marginalized groups the opportunity to gain access to assistance and is empowered independently to improve their standard of living.Keywords: Poverty; Self-Help Housing Program; Standard of Family LivingAbstrakTujuan studi literatur ini adalah untuk mengetahui dampak lokal, nasional, dan global yang dihasilkan dari program Rumah Swadaya dalam mengentaskan kemiskinan. Rumusan masalah dalam makalah ini yakni:Apa dampak lokal, nasional, dan global yang dihasilkan dari Program Rumah Swadaya dalam mengentaskan kemiskinan?”. Riset ini merupakan studi literatur terhadap dokumen-dokumen yang berkaitan dengan Program Rehabilitasi Sosial Rumah Tidak Layak Huni Untuk Pengentasan Kemiskinan. Kesimpulan dari studi yakni program Rumah Swadaya berdampak positif pada pengentasan kemiskinan dan mensejahterakan keluarga miskin melalui pengangkatan kualitas/ taraf hidup keluarga tersebut. Program Rumah Swadaya juga secara tidak langsung menghapuskan kelompok marginal dimana memberi kesempatan kelompok marginal untuk mendapatkan akses bantuan dan berdaya secara mandiri dapat memperbaiki taraf hidupnya.Kata kunci: kemiskinan; program rumah swadaya;taraf hidup keluarga